2008
DOI: 10.1080/02640410802526924
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of a training session during Ramadan in fasting and non-fasting Tunisian youth football players

Abstract: Heart rate was measured in 79 young male soccer players during training in the third week of Ramadan. Forty-eight players were practising Ramadan fasting, while the other 31 players were eating normally. All participants trained for 60-80 min at an ambient temperature of 25-28 degrees C and relative humidity of 50-53%. Heart rate, which was measured throughout the training session, was marginally higher in the fasting (mean 144 beats . min(-1), s = 25) than in the non-fasting (139 beats . min(-1), s = 23) grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Both groups assessed the required effort of training as being ''somewhat hard'' and the same relative number of players found training to be ''normal'' (56%), ''hard'' (17%), and ''easy'' (27%) throughout the study (Leiper, Watson, Evans, & Dvorak, 2008c). Circulating transferrin concentrations generally increased during Ramadan in the present study, and returned to baseline values 3 weeks after Ramadan.…”
Section: Discussionsupporting
confidence: 45%
“…Both groups assessed the required effort of training as being ''somewhat hard'' and the same relative number of players found training to be ''normal'' (56%), ''hard'' (17%), and ''easy'' (27%) throughout the study (Leiper, Watson, Evans, & Dvorak, 2008c). Circulating transferrin concentrations generally increased during Ramadan in the present study, and returned to baseline values 3 weeks after Ramadan.…”
Section: Discussionsupporting
confidence: 45%
“…Aspects of physical performance are compromised, but the deterioration is often not marked, and other aspects are unaffected. For example, in soccer players, a deterioration in Vo 2 max but not sprinting ability or agility,4 a fall in aerobic capacity, endurance and jumping ability but no change to sprinting or agility,5 a decreased ability to perform exercise at 75% Vo 2 max,6 no clear changes in speed, power, agility, endurance and dribbling skills,7 a marginally reduced (but biologically non-significant) decrease in maximal heart rate but no change in perceived exertion,8 and a general decrease in fitness and tests of skill (speed, agility, dribbling and endurance)9 have all been reported. In addition, some studies indicated that subjective assessments of performance had been performed less well9 or that the exertion required to undertake the training sessions was increased 10 11.…”
Section: Changes In Performance In Ramadanmentioning
confidence: 99%
“…For a long time, it has been suggested that the alteration of eating habits and lifestyle imposed by the Ramadan intermittent fast may require a reduction in the training load undertaken by elite Muslim athletes 2426. It is therefore common practice for coaches and conditioning professionals to reduce training demands during Ramadan intermittent fast, in the belief that this will allow their athletes to better cope with training while following their religious demands (see figure 1).…”
Section: Ramadan Intermittent Fast: Training Cessation Reduced Trainmentioning
confidence: 99%
“…It is therefore common practice for coaches and conditioning professionals to reduce training demands during Ramadan intermittent fast, in the belief that this will allow their athletes to better cope with training while following their religious demands (see figure 1). 19 22 25 This could potentially result in the occurrence of detraining before important competitive events, particularly with high level athletes 22 25. To better understand the potential threat of a drastic reduction in training or training cessation, the following section reviews the main physiological and performance alterations accompanying training stoppage.…”
Section: Ramadan Intermittent Fast: Training Cessation Reduced Trainmentioning
confidence: 99%
See 1 more Smart Citation